Global trends in tumor microenvironment-related research on tumor vaccine: a review and bibliometric analysis - Liu, Ying; Li, Sixin; Chen, Lu; Lin, Lin; Xu, Caijuan; Qiu, Huiwen; Li, Xinyu; Cao, Hui; Liu, Kun (Frontiers in Immunology, 2024)
Background Tumor vaccines have become crucial in cancer immunotherapy, but, only a limited number of phase III clinical trials have demonstrated clinical efficacy. The crux of this issue is the inability of tumor vaccines to effectively harmonize the tumor microenvironment with its intricate interplay. One factor that can hinder the effectiveness of vaccines is the natural immunosuppressive element present in the tumor microenvironment. This element can lead to low rates of T-cell response specific to antigens and the development of acquired resistance. Conversely, anticancer vaccines alter the tumor microenvironment in conflicting manners, inducing both immune activation and immunological evasion. Hence, comprehending the correlation between tumor vaccines and the tumor microenvironment would establish a foundation for forthcoming tumor treatment. Objective Our review explores the realm of research pertaining to tumor vaccinations and the tumor microenvironment. Our objective is to investigate the correlation between tumor vaccines and the tumor microenvironment within this domain. We then focus our review on the dominant international paradigms in this research field and visually illustrates the historical progression and emergent patterns observed in the past. Methods From January 1, 1999 to February 7, 2023, 1420 articles on the interplay between tumor vaccines and the tumor microenvironment were published, according to The Clarivate Web of Science (WOS) database used in our review. A bibliometric review was designed for this collection and consisted of an evaluation. The evaluation encompassed various discernible attributes, including the year of publication, the journals in which the articles were published, the authors involved, the affiliated institutions, the geographical locations of the institutions, the references cited, and the keywords employed. Results Between the years 1999 and 2022, publications saw a significant increase, from 3 to 265 annually. With 72 papers published, Frontiers in Immunology had the most manuscripts published. The Cancer Research publication garnered the highest number of citations, amounting to 2874 citations. The United States exerts significant dominance in the subject, with the National Cancer Institute being recognized as a prominent institution in terms of both productivity and influence. Furthermore, Elizabeth M. Jaffee was recognized as the field’s most prolific and influential author with 24 publications and 1,756 citations. The co-occurrence cluster analysis was conducted on the top 197 keywords, resulting in the identification of five distinct clusters. The most recent high-frequency keywords, namely immune therapy, dendritic cell, tumor microenvironment, cancer, and vaccine, signify the emerging frontiers in the interaction between tumor vaccines and the tumor microenvironment. Conclusion Our review uncovers insights into contemporary trends, global patterns of collaboration, fundamental knowledge, research areas of high interest, and emerging frontiers in the field of TME-targeted vaccines.